2015
DOI: 10.3928/01477447-20151120-06
|View full text |Cite
|
Sign up to set email alerts
|

Medialized Versus Lateralized Center of Rotation in Reverse Shoulder Arthroplasty

Abstract: Reverse shoulder arthroplasty may be performed using components that medialize or lateralize the center of rotation. The purpose of this prospective study was to directly compare 2 reverse shoulder arthroplasty designs. Two treatment groups and 1 control group were identified. Group I comprised 9 patients using a medialized Grammont-style (GRM) prosthesis with a neck-shaft angle of 155°. Group II comprised 9 patients using a lateralized (LAT) prosthesis with a neck-shaft angle of 135°. Pre- and postoperative a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

2
27
0
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 41 publications
(30 citation statements)
references
References 24 publications
2
27
0
1
Order By: Relevance
“…A prospective study with a few patients demonstrated that different humeral designs produce radiographically different anatomy, with 135 lateral design preserving some anatomic relationships; this may have an effect on ROM, with traditional designs achieving greater forward flexion and lateralized designs achieving greater external rotation. 44 A recent study by Merolla et al 37 showed similar postoperative ROM between Grammont humeral design and curved stem, even though the onlay humeral implant with 145 neck-shaft angle was associated with significantly greater delta scores of external rotation; the same study, after a subgroup analysis, showed no differences in any plane of shoulder mobility between the subset of patients who received the BIO-RSA component and the Ascend Flex group without glenoid bone grafting. According to these conclusions, our clinical study demonstrates that overall, BIO-RSA does not increase ROM in any movement if it is associated with a 145 neck-shaft angle stem, and humeral lateralization alone may be sufficient to improve ROM.…”
Section: Discussionmentioning
confidence: 91%
See 1 more Smart Citation
“…A prospective study with a few patients demonstrated that different humeral designs produce radiographically different anatomy, with 135 lateral design preserving some anatomic relationships; this may have an effect on ROM, with traditional designs achieving greater forward flexion and lateralized designs achieving greater external rotation. 44 A recent study by Merolla et al 37 showed similar postoperative ROM between Grammont humeral design and curved stem, even though the onlay humeral implant with 145 neck-shaft angle was associated with significantly greater delta scores of external rotation; the same study, after a subgroup analysis, showed no differences in any plane of shoulder mobility between the subset of patients who received the BIO-RSA component and the Ascend Flex group without glenoid bone grafting. According to these conclusions, our clinical study demonstrates that overall, BIO-RSA does not increase ROM in any movement if it is associated with a 145 neck-shaft angle stem, and humeral lateralization alone may be sufficient to improve ROM.…”
Section: Discussionmentioning
confidence: 91%
“…However, only 2 clinical studies compared a 155 angle implant with a lower angle implant, showing little improvement in external rotation and a lower rate of scapular notching. 37,44 On the other hand, glenoid lateralization can be achieved with a metallic device (metallic increased-offset RSA) or with bone graft (bony increased-offset [BIO] RSA) positioned under the baseplate. Compared with a standard Grammont reverse prosthesis, lateralization of the glenosphere in addition to the increased lateral offset has the important biomechanical consequence of moving the center of rotation laterally, with potential effect on clinical outcomes.…”
mentioning
confidence: 99%
“…Several clinical studies have compared the differences in outcomes among RSA designs with different centers of rotation. Streit et al compared the outcomes for 9 patients who received a medialized, Grammont-style prosthesis with those for 9 patients who were treated with a prosthesis with a lateralized center of rotation 14 . Postoperative external rotation was shown to be greater in the lateralized group (35°) than in the medialized group (28°), although the difference was not significant (p = 0.07), possibly because of the small number of patients in the study.…”
Section: Discussionmentioning
confidence: 99%
“…RSA designs with a more lateralized center of rotation could potentially restore external rotation without the need for a latissimus dorsi transfer. Several clinical studies and virtual shoulder models have indicated that such designs can improve external rotation by allowing greater impingement-free motion and by retensioning the remaining rotator cuff and posterior aspect of the deltoid 10 - 14 . However, to our knowledge, no study to date has focused on the subset of patients with a preoperative external rotation deficit.…”
mentioning
confidence: 99%
“…Another important aspect from the results is the increased lateralization which onlay designs produce (83% increase compared to inlay design). Even though, lateralized centre of rotation in reverse shoulder arthroplasty is associated with better external rotation [23], biomechanical and clinical studies advocate that highest moment arms of the deltoid muscle in reverse shoulder prosthesis occur with a medialized joint centre [1-3, 4, 5, 22, 25]. Further studies that determine the function of the deltoid with these different designs are desirable.…”
Section: Discussionmentioning
confidence: 99%